Research on Child-Rearing Support for Fathers Required from Nursery school Childcare Workers - Yasuhiro Okamura (Budapest International Research and Critics University, 2023)
This study aimed to clarify the type of parenting support required by day care center nursery staff for fathers whose children are enrolled in these centers. In this study, ten fathers who met the selection criteria were interviewed, and their data were analyzed using the systematic cause analysis technique. The storylines were divided into “support for raising one’s own child,” “provision of knowledge about children,” “opportunities for socialization among parents,” and “support tailored to individual needs.” Although fathers saw day care centers as child-rearing centers, other facilities were not deemed social resources for fathers’ child-rearing support. Therefore, day care centers and childcare providers must create an environment conducive enough for fathers to feel comfortable approaching them as a social resource regarding child-rearing support. In light of the aforementioned, day care center nursery providers must foster a climate where fathers feel comfortable approaching them for social support. In doing so, it became clear that the social work principle of intervening at the point of contact where people and the environment interact and providing support based on individualization as well as providing specific support, such as childcare workers, should be involved in a way that fathers feel they can consult with them.